Pengaruh Kualitas Pelayanan Terhadap Kepuasan dan Loyalitas Pelanggan Pada Ramayana Department Store di Kota Denpasar - Prayoga, Bayu Putra; Kusumadewi, Ni Made Wulandari; Suryani, Alit (E-Jurnal Manajemen, 2014)
this study aims to determine the effect of service quality on customer satisfaction and loyalty in the Ramayana Department Store in the city of Denpasar. Number of respondents were 120 respondents using purposive sampling technique with criteria respondent with high school/ equivalent education, have visited and shopped in the Ramayana Department Store Denpasar at least 3 times a month. This research using path analysis with SPSS.  The results showed positive and significant effect of service quality on customer satisfaction, positive and significant effect of service quality on customer loyalty ,positive and significant effect of customer satisfaction on customer loyalty in Ramayana Department Store.   Kata Kunci : sevice quality,customer satisfaction, customer loyalty
Keywords: sevice quality,customer satisfaction, customer loyalty